2006
DOI: 10.3346/jkms.2006.21.4.656
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations in Primary Gastric Carcinomas Correlated with Clinicopathological Variables by Array Comparative Genomic Hybridization

Abstract: Genetic alterations have been recognized as an important event in the carcinogenesis of gastric cancer (GC). We conducted high resolution bacterial artificial chromosome array-comparative genomic hybridization, to elucidate in more detail the genomic alterations, and to establish a pattern of DNA copy number changes with distinct clinical variables in GC. Our results showed some correlations between novel amplified or deleted regions and clinical status. Copy-number gains were frequently detected at 1p, 5p, 7q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Gain of 20q12-1q13, where MMP-9 is located, has been reported to be one of the most frequent regions with genomic gains in gastric cancer (15 -18). Moreover, several reports suggested that the gain at 20q was related to lymph node metastasis of gastric cancer (19,20). Whereas the progression of gastric cancer is obviously influenced by the quantitative changes in MMP-9 expression, the effects of qualitative changes (variations in amino acid sequence) are largely unknown.…”
Section: Matrix Metalloproteinases (Mmp) Have Been Well Documentedmentioning
confidence: 99%
“…Gain of 20q12-1q13, where MMP-9 is located, has been reported to be one of the most frequent regions with genomic gains in gastric cancer (15 -18). Moreover, several reports suggested that the gain at 20q was related to lymph node metastasis of gastric cancer (19,20). Whereas the progression of gastric cancer is obviously influenced by the quantitative changes in MMP-9 expression, the effects of qualitative changes (variations in amino acid sequence) are largely unknown.…”
Section: Matrix Metalloproteinases (Mmp) Have Been Well Documentedmentioning
confidence: 99%
“…Previous studies have revealed a complex portrait of recurring chromosomal amplifications and deletions in GC, including gains and losses at chromosomes 1q, 8q, 17q, and 20q (2)(3)(4). The recurrent nature of these aberrations has been attributed to the presence of genes important for gastric carcinogenesis, such as CD44 at 11p13, CCNE1 at 19q13, and BTAK at 20q13 (5-7).…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic and molecular biological studies of human cancers have identified chromosomal abnormalities, including partial deletions of specific loci (Wang et al, 1998;Senchenko et al, 2004). Furthermore, allelotyping studies performed on solid tumors involving loss of heterozygosity (LOH) using cytogenetic techniques, such as fluorescence in situ hybridization (FISH) and comparative genomic hybridization (CGH), have demonstrated genomic alterations in gastric cancer at specific regions and copy number losses in regions containing tumor suppressor genes (Sakakura et al, 1999;Kang et al, 2006;Takada et al, 2006). These findings suggest that complicated genetic alterations contribute to gastric carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%